Glosa do wyroku Sądu Unii Europejskiej z 9 lutego 2022 r. w sprawie T-791/19 – Sped-Pro S.A. przeciwko Komisji Europejskiej – „Zasada państwa prawnego a współpraca krajów członkowskich Unii Europejskiej w obszarze ochrony konkurencji” - Kłopocki, Kamil (Studia Prawa Publicznego, 2023)
The aim of this case comment is to discuss whether it was justified that the General Court in its judgment dated 9 February 2022 in the case Sped-Pro (T-791/19) annulled the European Commission’s Decision No. C(2019) 6099 final dated 12 August 2019 r. (case AT.40459) connected to the potential abuse by PKP Cargo of a dominant position on the market for rail freight in Poland. In this judgement, the General Court argued on the basis of the rule of law principle and applied analogically the judgment on the European Arrest Warrant. In this regard, the analysis starts with the rule of law principle, the judicial independence of courts and administrative authorities, the obligation of loyal cooperation between European Union and member states to ensure fulfilment of the obligations arising out of this Treaty, both in the light of Union law and European courts case law.The next part of this case comment attempts to assess whether the General Court was justified in analogically applying the judgement dated 25 VII 2018 r. C-216/18 PPU Minister for Justice and Equality on the European Arrest Warrant in the field of European policy on competition. The analysis ends with the description of the practical consequences of the Commission’s finding that the President of UOKiK and the Court of Competition and Consumer Protection are not independent. In the last part of the text, the author also indicates the consequences of the proper implementation of the Directive ECN+ for analysing the scope of independence of the President of the Office of Competition and Consumer Protection. The author indicates the necessity to separate in future analysis the issue of the independence of the President of the Office of Competition and Consumer Protection (national administrative competition authority) and the Court of Competition and Consumer Protection, which in Polish is a common court.